The Effect of Financial Performance on Stock Returns in Manufacturing Companies Listed on the IDX for the 2018-2022 Period - Nasrullah Nasrullah; Abdul Khaliq; Sultan Sarda; Aulia Aulia; Hamzah Dwi Julianto (Jurnal Ilmu Manajemen Profitability, 2023)
This research is a type of quantitative research with the aim of knowing the effect of financial performance on stock returns in manufacturing companies listed on the IDX for the 2018-2022 period. The samples in this study were 6 manufacturing companies listed on the IDX for the 2018-2022 period. Sampling technique using purposive sampling technique. The type of data used is secondary data. The research data was obtained from the company's financial reports published on the website www.idx.co.id  . The data analysis method used in this study is descriptive analysis, classical assumption test and multiple linear regression using statistical calculations through SPSS version 24. Based on the results of the study, it shows that the Current Ratio (CR) and Return on Assets (ROA) variables have a significant effect on Stock Returns, while the Debt to Equity Ratio (DER) and Return on Equity (ROE) variables have no significant effect on Stock Returns. Companies should improve their financial performance so that investors are interested in investing